A Study of Determining Factors Influencing the Intention of Cryptocurrency Investors Using UTAUT 2 Approach - Ladia Puspanegara; Jono M. Munandar; Bagus Sartono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
In the past few years, the Indonesian cryptocurrency market has experienced significant growth, reflecting the country's increasing popularity and adoption of cryptocurrencies. This study aims to identify the factors that influence consumer behavior in adopting cryptocurrency technology, utilizing the unified theory of acceptance and use of Technology (UTAUT 2) model as the theoretical framework. This study proposes the utilization of UTAUT 2 due to its robustness and enhanced explanatory capability compared to the original UTAUT model. The UTAUT 2 model is expanded by incorporating perceived risk. This study involved 248 respondents who are cryptocurrency users from the Indonesian cryptocurrency community on the Facebook and Telegram platforms. The sampling method used was purposive sampling by distributing questionnaires using online forms and Google Forms.“The data were analyzed using two methods,“descriptive statistical analysis and SEM (Structural Equation Modeling).”The research findings indicate that several variables such as price value, social influence, hedonic motivation, performance expectancy, effort expectancy, and facilitating conditions have a positive and significant influence on BI (Behavioral Intention).”Additionally, the perceived risk variable has a negative and significant influence on behavioral intention.